THE EQUITY, DIRECT MATERIALS, DIRECT LABOR, PRODUCTION COST, AND PROMOTION COST: HOW THESE CAN EFFECT TO REVENUE-SHARIA PERSPECTIVE - Ristu Dwi Putri; Dianita Meirini (State Islamic Institute (IAIN) Tulungagung, 2022)
Abstract: This study aims to to 1. Test the significance of the effect of capital on the business ncome of Yon Vandel Marble Craftsman. 2. Testing the significance of the nfluence of raw materials on the business ncome of Yon Vandel Marble Craftsman. 3. Testing the significance of the effect of labor wages on the business ncome of Yon Vandel Marble Craftsman. 4. Testing the significance of the effect of production on the business ncome of Yon Vandel Marble Craftsman. 5. Testing the significance of the effect of promotion costs on the business ncome of Yon Vandel Marble Craftsman. 6. To examine the significance of the effect of capital, raw materials, labor wages, production and promotion costs simultaneously on the business ncome of Yon Vandel Marble Craftsman.This study uses a quantitative approach with the type of associative research. The sampling technique used a saturated sampling technique with a total sample of 36 quarterly financial statements of Yon Vandel Marble Craftsman 2011-2019. This study uses secondary data. The measurement scale n this study uses a ratio scale. The data analysis method used s multiple linear regression analysis. The results of this study are 1. Capital partially has a significant positive effect on the business ncome of Yon Vandel Marble Craftsmen. 2. Partial raw materials have a positive but not significant effect on the business ncome of Yon Vandel Marble Craftsman. 3. Labor wages partially have a significant positive effect on the business ncome of Yon Vandel Marble Craftsman. 4. Production partially has a positive but not significant effect on the business ncome of Yon Vandel Marble Craftsman. 5. Promotional costs partially have a positive but not significant effect on the business ncome of Yon Vandel Marble Craftsman. 6. Capital, raw materials, labor wages, production and promotion costs together have a significant positive effect on the business ncome of Yon Vandel Marble Craftsman. Keywords: Raw Materials, Promotional Costs, Capital Income, Production, Labor Wages, Micro Enterprises